Variations in Food of Largehead Hairtail Fish (Trichiurus lepturus) In the Kolono Bay Waters East Kolono District South Konawe Regency - Sri Aswanti Nun Sugian; Asriyana Asriyana; Halili Halili (Jurnal Manajemen Sumber Daya Perairan, 2022)
Trichiurus lepturus are commonly known as largehead hairtail fish. These fish generally live in subtropical to tropical climate areas that spread from north of the equator to the south of the equator. T. lepturus generally lives in bottom waters and usually vertical migration (benthopelagic) and migration to river mouths at a young stage (amphidromous). In general, this species lives in waters with a depth of 0-400 meters. This study aims to analyze variations in the types of fish food largehead hairtail fish  in the water of Kolono Bay. The research was carried out from February to My 2020 in the waters of the Kolono Bay. Analysis of fish food habits using the data analysis method of Index Stomach Content, Indeks of Propenderance, niche breadth and overlap. The results showed that the type of food for largehead hairtail fish (T. lepturus) in the waters of Kolono Bay was the most common type of Engraulidae, then Clupeidae and the least species of Loliginidae, Mullidae, Gerreidae and Crustacea.